Lumbar support system - Salit, Mohd Sapuan; Ismail, Mohd Yusof; Ismail, Napsiah; Karuppiah, Karmegam (2012)
A lumbar support system for providing comfort to a driver of an open air vehicle having at least two wheels includes a lumbar support configured to be mounted proximate a center portion of a seat of the vehicle, a central body having a first end and a second end, a supporting means configured to couple the lumbar support to the central body, a seat fixing means for mounting the upper portion on the seat of the vehicle, a first engagement means for coupling the seat fixing means to the seat of the vehicle, and a second engagement means for coupling the system to the seat of the vehicle. The second engagement means includes a second shaft and a bottom plate.